Implementing of Students Character Education in SDN 0605 Simanuldang KKN 174 UINSU Simanuldang Jae Village - Ali Darta; Alumni Harahap; Amir Husin Lubis; Asmaria Hasibuan; Tri Wulan Hasibuan (Universitas Muhammadiyah Enrekang, 2022)
Character education is the initial foundation needed in building a nation. Therefore, schools have an obligation to be committed to building the nation's character. In this case, of course, there are many challenges that need to be faced, one of which is the development of technology and information as a result of globalization. Modern lifestyles that influence attitudes and behavior unwittingly deviate from the values ​​and noble values ​​of the Indonesian nation. This study is to describe the character values ​​developed in SDN 0605 Simanuldang in the implementation of character education and the obstacles in implementing character education in SDN 0605 Simanuldang. This type of research is descriptive using a quantitative approach. The data collection method used in this study was interviews. The data analysis used is collecting data, reducing data, then presenting it to draw conclusions. The results showed that the character values ​​developed at SDN 0605 Simanuldang consisted of 13 characters, namely religious, honest, tolerant, disciplined, democratic, national spirit, love for the homeland, appreciating achievement, friendly, fond of reading, caring for the environment, social care, and responsibility. answer. Implementation of character education through the learning process, school rules and extracurricular implementation. There are obstacles in implementing character education at SDN 0605 Simanuldang, namely digital games, unfavorable house boundaries, the influence of TV viewing, and lack of understanding of student character.